2018
DOI: 10.1002/ps.4834
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of imidacloprid resistance in the bird cherry‐oat aphid, Rhopalosiphum padi, a serious pest on wheat crops

Abstract: Multiple mechanisms confer imidacloprid resistance in R. padi. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 60 publications
5
56
0
Order By: Relevance
“…Cytochrome P450 enzyme levels were measured using the heme peroxidation method (Wang et al, 2018;William and Janet, 1997). Briefly, the total reaction volume was 650 μl, consisting of enzyme sample (40 μl), potassium phosphate buffer (160 μl, 0.625 M, pH 7.0), 50 μl H 2 O 2 (3%) and 400 μl of 3,3',5,5'-tetra-methylbenzidine (TMBZ) solution (Sigma…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%
“…Cytochrome P450 enzyme levels were measured using the heme peroxidation method (Wang et al, 2018;William and Janet, 1997). Briefly, the total reaction volume was 650 μl, consisting of enzyme sample (40 μl), potassium phosphate buffer (160 μl, 0.625 M, pH 7.0), 50 μl H 2 O 2 (3%) and 400 μl of 3,3',5,5'-tetra-methylbenzidine (TMBZ) solution (Sigma…”
Section: Enzyme Activity Assaysmentioning
confidence: 99%
“…The control of this aphid has depended largely on the use of chemically synthesized pesticides, 20 such as imidacloprid, which is a neonicotinoid that targets sucking pests, such as aphids and the green leaf bug. 21 It has been widely applied in wheat fields to control wheat aphid in China. As a result, S. avenae has developed serious resistance to imidacloprid.…”
Section: Introductionmentioning
confidence: 99%
“…Imidacloprid, a hloronicotinyl insecticide that targets aphids, leafhoppers, whiteflies and other sucking pests, has been widely used for the control of wheat aphid in China. Consequently, wheat aphid has evolved serious resistance to imidacloprid . Previous studies have demonstrated that metabolic and target‐site mechanisms are associated with imidacloprid resistance in many insect pests .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, wheat aphid has evolved serious resistance to imidacloprid. [6][7][8][9] Previous studies have demonstrated that metabolic and target-site mechanisms are associated with imidacloprid resistance in many insect pests. 10,11 For example, the R81T mutation of the nAChR 1 subunit confers resistance to imidacloprid in cotton aphid 5,[12][13][14] and overexpression of P450 genes is associated with imidacloprid resistance in Nilaparvata lugens and Leptinotarsa decemlineata.…”
Section: Introductionmentioning
confidence: 99%